Learning predictive analytics with python gain practical insights into predictive modelling by implementing Predictive Analytics algorithms on public datasets with Python - Kumar, Ashish (2016)
Annotation
Includes index. - Online resource; title from PDF title page (EBSCO, viewed September 8, 2017)
Keywords: Python (Computer program language); Python (Langage de programmation); COMPUTERS; Programming Languages; Python